1981
DOI: 10.1177/002224378101800103
|View full text |Cite
|
Sign up to set email alerts
|

Advertising and Public Policy: The Macroeconomic Effects of Advertising

Abstract: Four research traditions on the effects of advertising are identified, and one of them—the tradition of macroeconomic studies—is carefully differentiated from the other three. A review of this macro tradition is undertaken to retrace the kinds of questions raised about the macro effects of advertising, evaluate the statistical procedures used to ascertain the causal nature of macro advertising relationships, and specify the ideal research design for studying advertising macro effects. Moving toward the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Causality in both Nicosia (1981) prewhitening and directions between Sims test advertising and aggregate consumption. Leone (1983) Frequently Double Advertising has primary purchased prewhitening and selective demand grocery effects.…”
Section: Doublementioning
confidence: 99%
See 1 more Smart Citation
“…Causality in both Nicosia (1981) prewhitening and directions between Sims test advertising and aggregate consumption. Leone (1983) Frequently Double Advertising has primary purchased prewhitening and selective demand grocery effects.…”
Section: Doublementioning
confidence: 99%
“…Using the Sims method, Jacobson and Nicosia (1981) established a contemporaneous relation between annual advertising and personal consumption in the u.K., plus one-year lagged effects in both directions. Using the Sims method, Jacobson and Nicosia (1981) established a contemporaneous relation between annual advertising and personal consumption in the u.K., plus one-year lagged effects in both directions.…”
Section: Doublementioning
confidence: 99%
“…The paradigm encompasses elements of lobbying, propagandizing, publicizing and negotiation . 53) as well as advertising (Bogart, 1978;Jacobsen and Nicosia, 1981). It also incorporates the work on international marketers as change agents (Thorelli, 1966;Hill and Still, 1980) and social marketing, which has been developing along its own path (Kotler and Zaltmann, 1971;Levy and Zaltman, 1975, ch.…”
Section: Seven Paradigms Of Marketing Wisdommentioning
confidence: 99%
“…Verdon, McConnell, and Roesler (1969) were the first to study the causal relationship between advertising and GNP, but their research was inconclusive. Causality was detected in a study by Taylor and Weiserbs (1972) and confirmed by some recent studies (Jacob & Nicosia, 1981;Jung & Seldon, 1995). However, consensus on the causal relationship between advertising and consumption has not been reached among researchers.…”
mentioning
confidence: 88%